2015
DOI: 10.1039/c4ra12075b
|View full text |Cite
|
Sign up to set email alerts
|

Detection of NaCN in aqueous media using a calixarene-based fluoroionophore containing ruthenium(ii)-bipyridine as the fluorogenic unit

Abstract: A new molecular sensor containing calixarene and ruthenium(II)-bipyridine as fluorophore bridged by amide moiety has been synthesised, characterized and its anion binding property has been investigated. It selectively detects cyanide in 95:5 water-acetonitrile when sodium salts of various anions such as F -, Cl -, Br -, I -, PO 4 2-, IO 4 -, BO 3 -, CH 3 COO -, CN -and SO 4 2-were used for investigation. The recognition event was monitored by fluorescence spectroscopy and the lower detection limit found is 70 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…More recently, Maity et al reported a ruthenium(II)-bipyridine-substituted calix[4]arene sensor 20 for the detection of CN − ( Figure 10 ) [ 93 ]. Of a range of sodium salts tested, NaCN alone led to fluorescence quenching and a blue-shift of the emission band at 624 nm (in 95:5 H 2 O:MeCN).…”
Section: Calixarene-based Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Maity et al reported a ruthenium(II)-bipyridine-substituted calix[4]arene sensor 20 for the detection of CN − ( Figure 10 ) [ 93 ]. Of a range of sodium salts tested, NaCN alone led to fluorescence quenching and a blue-shift of the emission band at 624 nm (in 95:5 H 2 O:MeCN).…”
Section: Calixarene-based Sensorsmentioning
confidence: 99%
“… Ruthenium(II)-bipyridine-substituted calix[4]arene sensor 20 is a turn-off probe for CN − , which causes fluorescence quenching and a blue-shift of the emission band at 624 nm [ 93 ]. The simple, polyanionic calix[4]arene-based sensor 21 is an ‘on-off’ probe for spermine 22 [ 94 ], while a QD-appended calix[8]arene receptor forms the complex 23 with C 60 fullerene, which quenches the QD fluorescence output [ 95 ].…”
Section: Figurementioning
confidence: 99%
“…2,5 Among the most classical luminescent metal complexes for the recognition of anions, Ru(II) complexes derived from bidentate bpy and/or phen-type ligands are particularly attractive because of their desirable photophysical, photochemical and electrochemical properties associated with the metal-to-ligand charge-transfer (MLCT) excited states. [35][36][37][38][39][40][41][42][43][44][45][46][47][48] However, chirality inherently introduced in the [Ru(bpy/phen) 3 ] 2+ type complexes leads to isomeric mixtures whose separation in most cases is very difficult. 49 On the other hand, the structurally more appealing [Ru(tpy) 2 ] 2+ type complexes derived from tridentate terpyridine-type ligands are achiral and are most suitable for the construction of linear rod-like systems by functionalization of the 4′-position of the tpy ligands.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] The chemotoxicity of the contrast medium frequently comes from the stability of the organic iodine. [7][8][9] This type of organic iodine is likely transformed to the ionic type by a redox reaction which may be catalyzed by metal ions in vivo. Primary research illustrating this reactivity can be easily realized through the study of organometallic reaction in vitro.…”
mentioning
confidence: 99%
“…However, several adverse effects caused by these contrast agents still happen sometimes in clinical application, including allergic‐type reactions, extravasations and renal toxicity . The chemotoxicity of the contrast medium frequently comes from the stability of the organic iodine . This type of organic iodine is likely transformed to the ionic type by a redox reaction which may be catalyzed by metal ions in vivo .…”
mentioning
confidence: 99%